Declining efficacy of artemisinin combination therapy against P. falciparum malaria on the Thai-Myanmar border (2003-2013): the role of parasite genetic factors - Pyae Phyo, A; Ashley, E; Anderson, T; Bozdech, Z; Carrara, V; Sriprawat, K; Nair, S; White, M; Dziekan, J; Ling, C; Proux, S; Konghahong, K; et al. (Oxford University Press, 2016)
Deployment of mefloquine-artesunate (MAS3) on the Thailand-Myanmar border has led to a sustained reduction in falciparum malaria, although antimalarial efficacy has declined substantially in recent years. The role of P. falciparum K13 mutations (a marker of artemisinin resistance) in reducing treatment efficacy remains controversial. Between 2003 and 2013, we studied the efficacy of MAS3 in 1005 patients with uncomplicated P. falciparum malaria in relation to molecular markers of resistance. PCR-adjusted cure rates declined from 100% in 2003 to 81.1% in 2013 as the proportions of isolates with multiple Pfmdr1 copies doubled from 32.4% to 64.7% and those with K13 mutations increased from 6.7% to 83.4%. K13 mutations conferring moderate artemisinin resistance (notably E252Q) predominated initially but these were later overtaken by propeller mutations associated with slower parasite clearance (notably C580Y). Infections with both multiple Pfmdr1 copy number and a K13 propeller mutation were 14 times more likely to fail treatment; PCR-adjusted cure rate was 57.8% (95% CI, 45.4, 68.3) compared to 97.8% (95% CI, 93.3, 99.3) in patients with K13 wild type and Pfmdr1 single copy. K13 propeller mutation alone was a strong risk factor for recrudescence (p=0.009). The combined population attributable fraction of recrudescence associated with K13 mutation and Pfmdr1 amplification was 82%. The increasing prevalence of K13 mutations was the decisive factor for the recent and rapid decline in efficacy of MAS3 on the Thailand-Myanmar border. These findings demonstrate the strong link between K13 mutations, Pfmdr1 amplification and ACT failure.